2017
DOI: 10.15282/jmes.11.3.2017.10.0261
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulse welding parameters on weld geometry of boron steel using low power fibre laser

Abstract: Demands of tailored weld blank application on press hardened materials such as boron steel have given interest in the process parameter study of laser welding. The pulse wave mode of laser welding produces high peak power, replacing the continuous wave mode which could lead to wider applications. Due to complications on the process parameter of PW mode, the study of parameter effect is needed. In this paper, the effect of PW welding parameters on weld geometry of boron steel using Fibre laser is presented. Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The PR value that was equal or closer to 1 indicated higher effective penetration, less undercut defect, and led to greater strength. Equation 2, (3), and (4) shows the calculation of depth actual, PR, and AR, respectively to determine the type of weld geometry [15] produced for the lowest and highest tensile strength sample (sample 1 and 9, respectively).…”
Section: Aspect Ratiomentioning
confidence: 99%
“…The PR value that was equal or closer to 1 indicated higher effective penetration, less undercut defect, and led to greater strength. Equation 2, (3), and (4) shows the calculation of depth actual, PR, and AR, respectively to determine the type of weld geometry [15] produced for the lowest and highest tensile strength sample (sample 1 and 9, respectively).…”
Section: Aspect Ratiomentioning
confidence: 99%
“…Cracking can arise in a uniform metallic material due to the fatigue caused by the exposure of continues stress and strain on it [1,2], and in weld areas where metallic parts are joined together by the welding processes [3,4]. Furthermore, it is reported that welding defects are the main cause of the catastrophic failure of the metallic structures such as in the gas pipeline system [5] and obtaining the optimised parameters for each welding process is one of the crucial steps to prevent defects [6][7][8]. It is worth to note that, cracking in the welding area can occur during and after the welding process due to hot and cold cracking, the formation of cavities, impurities inclusions such as oxides and non-metallic slag, lack of fusion, incomplete penetration and undercut [4].…”
Section: Introductionmentioning
confidence: 99%
“…but low strength material is used in the areas with less critical regions/geometry for the purpose of reducing the weight of a vehicle which in turn increases fuel economy without compromising the structural integrity of the car [1]. However, the application of high strength steels in automotive industry has been on the high side for centuries [2], but low carbon steels have also had its application in chassis and body panel of every road-worthy vehicles ranging from standard five-seaters to heavy duty trucks due to its high cost benefit, weldability, malleability, formability, high potential to be engineered in several ways to meet crash safety requirements etc. According to Razak and Shing [3], carbon steel is the most widely used engineering material and despite its low corrosion resistant property is still applicable in marine industries, construction and automotive industries, chemical and petroleum industries etc.…”
Section: Introductionmentioning
confidence: 99%